Per una mappatura del pensiero di Antonio Gramsci nel Sud del mondo Ricezione, traducibilità, declinazioni teoriche e praxis gramsciane - Manduchi, Patrizia; Marchi, Alessandra (Quaderni del GramsciLab, 2022)
This volume collects the results of the activities of the Hub for International Gramscian Studies (GramsciLab) and stems from the need, shared among colleagues from different scientific areas but united by specialization in historical-political and linguistic studies in specific area contexts, to proceed to a broader 'mapping' of the diffusion of Antonio Gramsci's thought. The focus is on countries in Asia, Africa and Latin America, where analyses and reflections on some important Gramscian analytical categories have been developing for decades with increasing vigor and surprising results, often little known, especially in Italy (not only for linguistic difficulties).